2017
DOI: 10.1371/journal.pcbi.1005747
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting ecology in drug pulse sequences in favour of population reduction

Abstract: A deterministic population dynamics model involving birth and death for a two-species system, comprising a wild-type and more resistant species competing via logistic growth, is subjected to two distinct stress environments designed to mimic those that would typically be induced by temporal variation in the concentration of a drug (antibiotic or chemotherapeutic) as it permeates through the population and is progressively degraded. Different treatment regimes, involving single or periodical doses, are evaluate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…Our approach is complementary to previous studies providing a detailed modeling of specific treatments [33,34,20,35,36,37,38]. Indeed, the majority of them [33,39,34,20,35,36,40] neglect stochastic effects, while they can have a crucial evolutionary impact [41,25,42]. The deterministic approach is appropriate if the number N of competing microbes satisfies N µ 1 1, where µ 1 is the mutation rate [43,41].…”
Section: Context and Perspectivesmentioning
confidence: 99%
“…Our approach is complementary to previous studies providing a detailed modeling of specific treatments [33,34,20,35,36,37,38]. Indeed, the majority of them [33,39,34,20,35,36,40] neglect stochastic effects, while they can have a crucial evolutionary impact [41,25,42]. The deterministic approach is appropriate if the number N of competing microbes satisfies N µ 1 1, where µ 1 is the mutation rate [43,41].…”
Section: Context and Perspectivesmentioning
confidence: 99%
“…In fact, recent work suggests that aggressive treatment strategies can hasten the emergence and spread of resistance [30][31][32][33][34][35][36][37][38][39][40][41]. In addition, numerous studies, both experimental and theoretical, provide evidence that less aggressive treatment strategies may be called for under some conditions [42][43][44][45][46][47][48][49][50], while several clinical trials have also demonstrated advantages of lower dose therapies [50][51][52][53][54][55][56][57][58]. The most frequently cited advantages of less aggressive therapies are reduced off-target selection for resistance and fewer adverse effects for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Using 387 a general stochastic model which includes variations of both composition and size of 388 the microbial population, we have shed light on the impact of periodic alternations of 389 presence and absence of antimicrobial on the probability that resistance evolves de novo 390 and rescues a microbial population from extinction. The majority of previous studies of 391 periodic antimicrobial treatments [10,[50][51][52][53][54][55] neglect stochastic effects, while they can 392 have a crucial evolutionary impact [13,15], especially on population extinction [18,20]. 393 In addition, established microbial populations are structured, even within a single 394 patient [56], and competition is local, which decreases their effective size, thus making 395 stochasticity relevant.…”
mentioning
confidence: 99%
“…This work opens many possible theoretical extensions. In particular, it will be very 431 interesting to include effects such as antibiotic tolerance, which tend to precede resis-432 tance under intermittent antibiotic exposure [4], as well as to consider the possibility of 433 concentrations above the mutant prevention concentration, such that resistant microbes 434 are also affected by the drug [4,54]. Another exciting extension would be to incorporate 435 spatial structure [60][61][62] and environment heterogeneity, in particular drug concentration 436 gradients.…”
mentioning
confidence: 99%